Dental and Emotional Perception in Individuals Affected by Amelogenesis Imperfecta - Murillo DDS, MSc, Gina (2015)
“Amelogenesis imperfecta” (AI) (prevalence up to 1 in 700) describes largely Mendelian enamel defects arising from gene mutations that present as structural  abnormalities of the temporary and permanent teeth as a result of defective enamel formation. AI has a wide range of clinical presentations and phenotypes and affects both sexes.  Despite increasing knowledge of the genetic mutations underlying AI there has been little research focussing on the effect of AI on the quality of life of AI patients. This study aimed to investigate the effects of AI on patient quality of life in a Costa Rican AI cohort. Affected family members were interviewed and their experiences used to develop an instrument (questionnaire) that was subsequently used to evaluate the impact of AI on their quality of life. 18 AI patients from 17 families were included in the study. Our findings showed that 100% had been teased and had suffered social rejection; 77.8% were concerned about their children´s inheritance and 66.7 % were concerned by the cost of treatment; 89% placed a high importance on their teeth. Results were not statistically significant when sorted by sex (p = 0.732).  The results of this study indicate that dental professionals need to understand AI not only as defective tooth enamel structure demanding specialist clinical management but also the negative impacts of the condition on the lives of their patients. This should be taken in to account when communicating with those affected.